Critical Thinking in Students’ Process of Writing the Argumentative Essay - Eka Anggraeny; Juang Rudianto Putra (Universitas Majalengka, 2017)
Abstract The basis of this study is to investigate the writing process done by the sixth semester students of English Department Jambi University in writing the argumentative essay and the challenges they found in the process of writing. In collecting the data, the researcher uses descriptive qualitative approach by inviting five participants to write an argumentative essay and to be interviewed afterwards. The researcher assesses essays using the checking list rubric and codes the data based on the research questions. The data are presented descriptively and are supported by the excerpts of essays, interviews, and related theories. The findings show that students have challenges in different aspects of key features in constructing the argument, which consist of: (1) position, (2) reasons or propositions, (3) a line of reasoning, (4) conclusion, (5) persuasion, and (6) signal words. The researcher also finds the challenges faced by the students through the interviews conducted. The challenges consist of: (1) The analysis and evaluation of content knowledge, (2) The writer’s development of position, and (3) The presentation of one position in coherent manner. As the result, this study is expected to help finding the way of how undergraduate students would be able to write an appropriate essay in academic context. The implications of the study and further research direction are also addressed. Keywords: Writing, Argumentative essay, Critical thinking